Cultural Analysis of Work to Improve Employee Work Productivity at the Landungsari Village Office, Dau District, Malang Regency - Jekson Kering Nyuru; R.Y Susanto; Fendiyatmi Kusufa (International Research & Development for Human Beings (IRDH), 2025)
Employee work productivity serves as a benchmark for every company in conducting its business activities, both in terms of product quality and quantity, especially in today's trade competition where companies must strive for quality and employee welfare, which becomes a competitive advantage over other companies. Additionally, employee work productivity is required to produce quality work in accordance with existing regulations and guidelines, thus yielding optimal work and achieving the set targets. This research aims to determine the influence of work culture on employee productivity at the Landungsari Village Office, Dau District, Malang Regency. This type of research employs a survey method with a quantitative descriptive approach and data analysis methods utilizing validity and reliability tests. The research results indicate that the work culture variable obtained a table value of 0.308, which concludes that all questionnaire items related to the work culture variable are deemed valid, and the employee performance productivity variable obtained a table value of 0.308, meaning that all questionnaire items related to the work culture variable are declared valid. The reliability test results on the work culture variable can be stated as reliable. This can be proven based on the Cronbach’s Alpha method (using statistical testing programs), which shows a Cronbach’s Alpha value of 0.782, greater than 0.06 (0.782 > 0.06), thus indicating that the reliability test on the work culture variable can be stated as reliable, and the reliability test on the employee productivity variable is also considered reliable. This can be proven based on the Cronbach’s Alpha method (using statistical testing programs) which shows that the Cronbach’s Alpha value is 0.801, which is greater than 0.06 (0.801 > 0.06), indicating that the reliability test on the variable of employee performance productivity can be stated as reliable.